Validity of multiplex-based assays for cytokine measurements in serum and plasma from “non-diseased” subjects: Comparison with ELISA - Dossus, Laure; Becker, Susen; Achaintre, David; Kaaks, Rudolf; Rinaldi, Sabina (Journal of immunological methods, 2009)
Multiplex-based immunoassays (MIA) allow the simultaneous measurement of different cytokines in small sample volumes, but their applicability in samples from “healthy” subjects, as those participating in large-scale epidemiological studies is not well known. We compared measurements of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-1 receptor antagonist (IL-1Ra), C-reactive protein (CRP) and soluble CD40L (sCD40L) obtained by MIA with those obtained by enzyme-linked immunosorbent assays (ELISA) in serum and plasma samples from 36 “healthy” subjects. We observed good correlations between measurements obtained by MIA and ELISA for IL-1Ra, CRP and sCD40L ( r > 0.80) but poor correlations for IL-6, TNF-α and IL-1β ( r < 0.40). When comparing MIA plasma and serum measurements, very high correlations were obtained for CRP ( r = 0.98) and fairly good correlations for IL-1Ra ( r = 0.60). In conclusion, multiplex-based assays can give an accurate estimate of the relative risk in large-scale epidemiological studies but only for cytokines that are present in relatively large concentrations (ng/mL).